DNA methyltransferase activity in the basolateral amygdala is critical for reconsolidation of a heroin reward memory - Qian, Shuyi; Shi, Cuijie; Huang, Shihao; Yang, Chang; Luo, Yixiao (Frontiers in Molecular Neuroscience, 2022)
The persistence of drug memory contributes to relapse to drug seeking. The association between repeated drug exposure and drug-related cues leads to cravings triggered by drug-paired cues. The erasure of drug memories has been considered a promising way to inhibit cravings and prevent relapse. The re-exposure to drug-related cues destabilizes well-consolidated drug memories, during which a de novo protein synthesis-dependent process termed “reconsolidation” occurs to restabilize the reactivated drug memory. Disrupting reconsolidation of drug memories leads to the attenuation of drug-seeking behavior in both animal models and people with addictions. Additionally, epigenetic mechanisms regulated by DNA methyltransferase (DNMT) are involved in the reconsolidation of fear and cocaine reward memory. In the present study, we investigated the role of DNMT in the reconsolidation of heroin reward memory. In the heroin self-administration model in rats, we tested the effects of DNMT inhibition during the reconsolidation process on cue-induced reinstatement, heroin-priming-induced reinstatement, and spontaneous recovery of heroin-seeking behavior. We found that the bilateral infusion of 5-azacytidine (5-AZA) inhibiting DNMT into the basolateral amygdala (BLA) immediately after heroin reward memory retrieval, but not delayed 6 h after retrieval or without retrieval, decreased subsequent cue-induced and heroin-priming-induced reinstatement of heroin-seeking behavior. These findings demonstrate that inhibiting the activity of DNMT in BLA during the reconsolidation of heroin reward memory attenuates heroin-seeking behavior, which may provide a potential strategy for the therapeutic of heroin addiction.